Factors Affecting Immune Responses in Honey Bees: An Insight - Kaur, Gurleen; Sharma, Rohit; Chaudhary, Ashun; Singh, Randeep (Journal of Apicultural Science, 2021)
Honey bees pollinate various crops and wild plants which ensures food security. However, in this modern world, bees are suffering. Decreasing global domesticated and wild bee populations while the demand for agricultural pollination services is increasing is a matter of concern. Colony losses are driven by such factors or interactions as changing environmental conditions, exposure to agrochemicals, parasite and pathogens attack and decreased flower abundance and diversity. All these stresses individually or together affect the immune system of bees and consequently bee fitness. Poor nutrition is the key stressor as it directly suppresses the immune system and reduces host resistance to other stressors. To cope with these stresses, honey bees have well-developed individual and social immune systems which initiate several defence reactions, but its activation, maintenance and use are detrimental for bee survival as it occurs at the cost of bee health. This review summarizes the causal factors and their possible interaction responsible for immune suppression in honey bees.